Youth Work in Tallinn: the Positive Impact on Young People - Taru, Marti (Studies of Transition States and Societies, 2010)
The article looks into youth work participation in Tallinn, the capital of Estonia. While the focus is on describing the link between participation in different activities and some characteristics of youth development, the article also describes youth work in Tallinn. The article looks at the link between participation in five distinct youth work activities (youth centres, hobby education, youth projects, youth organisations, counseling) and three outcome variables: labor market orientation, multiculturalism and youth voting. The empirical analysis is based on a database of 1061 elementary and secondary school pupils that was collected in Tallinn in spring 2010. Analysis results indicate a positive relationship between youth work participation and levels of the outcome variables. Thought not all regression coefficients were statistically significant, they consistently pointed in the same direction. The findings are interpreted as supporting the hypothesis that youth work participation does have a positive influence on youth development.